Amanda Rose Anderson Journal Entry on 50th Day of Quarantine - Anderson, Amanda Rose::::::::: (2020)
Journal entry from day 50 of shelter-in-place recounting infection rates, lockdown protests, and observations from a trip to Calaveras County.